Temporal trends in inpatient pediatric sleep apnea surgery: 1993–2010. (19th September 2016) - Smith, David F.; Sa, Ting; Fenchel, Matthew; Cohen, Aliza P.; Heubi, Christine; Shott, Sally R.; Gourin, Christine G.; Ishman, Stacey L.
Abstract : Objectives/Hypothesis: We sought to characterize changes in the patterns of inpatient surgical sleep care over time and ascertain if these changes were consistent with previously reported trends in adult surgical sleep care. Study Design: Repeated cross‐sectional study. Methods: Discharge data from the U.S. Nationwide Inpatient Sample for 125, 691 nasal, palatal, or hypopharyngeal procedures in children for sleep‐disordered breathing or obstructive sleep apnea (OSA) from 1993 to 2010 were analyzed using cross‐tabulations and multivariate regression modeling. Results: Inpatient surgical sleep procedures increased from 45, 671 performed in 1993 to 2000 (study period 1) to 80, 020 in 2001 to 2010 (study period 2). Overall, patients were commonly male (61.3%), privately insured (46.8%), 2 to 6 years old (39.4%), and white (36.4%). Obesity was reported in 4.6% and 6.7% of children during study periods 1 and 2, respectively ( P < .0001). Tonsillectomy (with and without adenoidectomy) was the most commonly performed procedure in both study periods. With the exception of uvulopalatopharyngoplasty and tracheostomy, all sleep procedures increased over time; however, multilevel surgery did not significantly increase ( P = .28). Children who underwent sleep surgery during study period 2 were more likely to receive a supraglottoplasty ( P = .0125) and to undergo procedures at high‐volume hospitals ( P = .0311), and less likely to undergo a tracheostomy ( P < .0001). Conclusions: These data reflect changing trends in the surgical management of pediatric OSA, with significant increases in nasal and hypopharyngeal procedures, particularly lingual tonsillectomy and supraglottoplasty. Unlike the trend in adults, multilevel surgery in children with sleep disordered breathing or OSA has not yet been integrated into routine clinical practice. Level of Evidence: 2C Laryngoscope, 127:1235–1241, 2017